COVID‐19: A perspective from Iran. Issue 5 (28th September 2020) - Ahmadi, Zargham H.; Mousavizadeh, Mostafa; Nikpajouh, Akbar; Bahsir, Mohamad; Hosseini, Saeid
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has presented unique challenges to healthcare systems the world over. The management of the current pandemic places a huge strain on healthcare sectors and demands new strategies on a global level. We herein review the latest epidemiologic data on the COVID‐19 pandemic, the Iranian healthcare system's response, and the impact on cardiac surgery practice in Iran.